Specific Features of Patients Under 40 Years Old With Small-to-Medium-Sized Arterial Deterioration - Matsubara, Kazuyoshi; Fukuhara, Natsumi; Hoshina, Katsuyuki; Miyahara, Kazuhiro; Suhara, Masamitsu; Taniguchi, Ryosuke; Matsukura, Mitsuru; Takayama, Toshio (Frontiers in Surgery, 2022)
Background Arterial deterioration is mostly caused by atherosclerosis, which progresses with age. However, we have observed serious backgrounds or etiologies in younger patients with non-atherosclerotic diseases and deterioration of small-to-medium-sized arterial lesions. Therefore, we aimed to identify the specific features of patients aged <40 years with deterioration of small-to-medium-sized arteries. Methods We selected patients who were admitted to our department from 1995 to 2019 with deterioration of small-to-medium-sized arteries (aneurysms, dissection, rupture, or arterial injury/damage) and focused on the cohort aged <40 years. We examined the backgrounds or etiologies of the patients including genetic and inflammatory diseases, which might have caused the arterial deterioration. Results Consequently, more than half (54.1%) of the patients aged <40 years had non-atherosclerotic comorbid diseases. However, the number of deteriorated arterial lesions was higher in patients aged <40 years than in patients aged ≥40 years (3.13 vs. 1.33 lesion/patient; P = 0.011). Furthermore, the data analysis of patients with multiple arterial lesions (≥3) revealed that the younger population tended to have more specific backgrounds or etiologies, notably Ehlers-Danlos syndrome and Behçet's disease. There were no differences in the all-cause mortality and cardiovascular disease-related mortality between patients aged <40 and ≥40 years (P = 0.89 and 0.29, respectively). Conclusions Over 50% of patients aged <40 years with deterioration of small-to-medium-sized arteries had non-atherosclerotic, specific clinical backgrounds or etiologies, including genetic and inflammatory diseases. In addition, they exhibited more arterial lesions than older patients.